Fast computation of the exact plasma dispersion functions - Pavlov, S.S.; Castejón, F.; Cappa, Á.; Tereshchenko, M. (Вопросы атомной науки и техники, 2009)
The paper is concerned with a computation of the exact relativistic plasma dispersion functions for complex argument z = x + iy in the region Q : y ≥ 0 on the base the theory of the continued fractions of Jacobi. It is first observed that these fractions represent those functions asymptotically for z → ∞ in the sector Q.